Does believing something to be fiction allow a form of moral licencing or a ‘fictive pass’ in understanding others’ actions? - Thompson, Jacqueline; Teasdale, Ben; van Emde Boas, Evert; Budelmann, Felix; Duncan, Sophie; Maguire, Laurie; Dunbar, Robin (Frontiers in Psychology, 2023)
The human capacity to engage with fictional worlds raises important psychological questions about the mechanisms that make this possible. Of particular interest is whether people respond differently to fictional stories compared to factual ones in terms of how immersed they become and how they view the characters involved and their actions. In this respect, an intriguing possibility is that fiction provides the audience with a ‘fictive pass’ that allows them to evaluate in a more balanced, neutral way the morality of a character’s behaviour. We use a randomised controlled experimental design to show that although knowing whether a film clip is fact or fiction does not affect how engaged with (‘transported’ by) a troubling story someone becomes, knowing that the story is fiction does grant them a ‘fictive pass’ to identify with a moral transgressor, and that this influences their views about the psychological causes of the transgressor’s behaviour.